Prescription Patterns and Outcomes of Patients With Atrial Fibrillation Treated With Direct Oral Anticoagulants and Warfarin: A Real-World Analysis. (September 2019) - Kattoor, Ajoe John; Pothineni, Naga Venkata; Goel, Akshay; Syed, Mahanazuddin; Syed, Shorabuddin; Paydak, Hakan; Mehta, Jawahar L.
Background: Direct oral anticoagulants (DOACs) have been found to be similar or superior to warfarin in reducing ischemic stroke and intracranial hemorrhage (ICH) in patients with atrial fibrillation (AF). We sought to examine the anticoagulation prescription patterns in community since the advent of DOACs and also evaluate the outcomes in terms of gastrointestinal (GI) bleeding, ischemic stroke, and ICH in real-world patients with AF receiving anticoagulation. Methods: This is a retrospective study comprising patients who were newly diagnosed with nonvalvular AF and were prescribed anticoagulants for stroke prevention. Prescription pattern of the anticoagulants based on CHA2 DS2 Vasc score was studied. Clinical outcomes of GI bleeding, ischemic stroke, and ICH were analyzed using a multivariate logistic regression model. Results: Of the 2362 patients with AF on anticoagulation, 44.7% were prescribed DOACs. Patients with CHA2 DS2 VASc score of ≥3 received a prescription for warfarin more often than DOACs ( P < .001). Multivariate logistic regression analysis revealed that the incidence of GI bleed (odds ratio [OR]: 0.91, 95% confidence interval [CI]: 0.62-1.35, P = .66) and stroke (OR: 0.77, 95% CI: 0.57-1.05, P = .10) was similar between warfarin and DOAC users. However, there was a trend toward lower ICH in the DOAC group (OR: 0.60, 95% CI: 0.36-1.01, P = .06). Conclusions: Prescription rate of DOACs for nonvalvular AF has increased significantly, with apixaban being the most commonly used agent. Patients with higher CHA2 DS2 -VASc score (≥3) are prescribed DOACs less often than warfarin. The reason for this discrepancy is unclear. Given the favorable risk–benefit profile of DOACs, further studies are needed to identify factors that determine anticoagulant selection in patients with AF with high thromboembolic risk.